ЗАНАБАЗАРЫН УРЛАГ БА ДУНДАД ЗУУНЫ ХОЖУУ ҮЕИЙН МОНГОЛД БУДДИЙН ШАШИНТ УЛС БАЙГУУЛСАН Hb - Ц. Уранчимэг (Acta Mongolica, 2013)
The article "Zanabazar’s art and the Building of Buddhist State in Late Medieval Mongolia *examines art of an eminent Mongolian Buddhist artist and scholar Zanabazar (1635-1723) who also was the First Jebtsundamba reincarnate mler of Mongolia. While some scholars have discussed Zanabazar’s art based on stylistic analysis (Tsultem 1982. Berger 1995). the issues of production and the choice of specific forms of deities have remained unclear. The article aims at illuminating Zanabazar’s artistic work within his mission of establishing a new Buddhist state in late Medieval Mongolia. Based on his surviving sculptures, his writings, and hagiographies, the article argues that Zanabazar did not consider any sectarian affiliations in his production; rather, he aimed at establishing a foundation for Vajrayena practice with Yoga Tantra deities for propagating Buddhism beyond nobility among broader masses for security and unity of his peoples.